Structural and Topographic Dynamics of Pulmonary Histopathology and Local Cytokine Profiles in Paracoccidioides brasiliensis Conidia-Infected Mice - Lopera, Damaris (Public Library of Science, 2011)
BACKGROUND: Paracoccidioidomycosis (PCM), an endemic systemic mycosis caused by the fungus Paracoccidioides brasiliensis (Pb), usually results in severe lung damage in patients. METHODS AND FINDINGS: Considering the difficulties to sequentially study the infection in humans, this work was done in mice inoculated intranasally with infective Pb-conidia. Lungs of control and Pb-infected mice were studied after 2-hours, 4, 8, 12 and 16-weeks post-infection (p.i) in order to define histopathologic patterns of pulmonary lesions, multiplex-cytokine profiles and their dynamics during the course of this mycosis. Besides the nodular/granulomatous lesions previously informed, results revealed additional non-formerly described lung abnormalities, such as periarterial sheath inflammation and pseudotumoral masses. The following chronologic stages occurring during the course of the experimental infection were defined: Stage one (2-hours p.i): mild septal infiltration composed by neutrophils and macrophages accompanied by an intense “cytokine burst” represented by significant increases in IL-1α, IL-1β, IL-4, IL-5, IL-6, IL-10, IL12p70, IL-13, IL-17, Eotaxin, G-CSF, MCP1, MIP1α, GM-CSF, IFN-γ, MIP1β and TNFα levels. Stage two (4-weeks p.i): presence of nodules, evidence of incipient periarterial- and intense but disperse parenchymal- inflammation, abnormalities that continued to be accompanied by hyper-secretion of those cytokines and chemokines mentioned in the first stage of infection. Stages three and four (8 and 12-weeks p.i.): fungal proliferation, inflammation and collagenesis reached their highest intensity with particular involvement of the periarterial space. Paradoxically, lung cytokines and chemokines were down-regulated with significant decreases in IL-2,IL-3,IL-5,IL-9,IL-13,IL-15,GM-CSF,IFN-γ,MIP1β and TNFα. Stage five (16-weeks p.i.): inflammation decreased becoming limited to the pseudotumoral masses and was accompanied by a “silent” cytokine response, except for PDGF, MIG, RANTES and IL12p40 which remained up-regulated for the duration of the experiment. CONCLUSIONS: Results of this study identified both classic and novel patterns corresponding to histopathologic and immunologic responses occurring during the course of experimental PCM.